Diffusion tensor imaging adds diagnostic accuracy in magnetic resonance neurography - Breckwoldt, Michael O.; Stock, Christian; Xia, Annie; Heckel, Andreas; Bendszus, Martin; Pham, Mirko; Heiland, Sabine; Bäumer, Philipp (Investigative radiology, 2015)
Objective - The aim of this study was to determine whether quantitative diffusion tensor imaging (DTI) adds diagnostic accuracy in magnetic resonance neurography. - Materials and Methods - This prospective study was approved by the institutional review board. We enrolled 16 patients with peripheral polyneuropathy of various etiologies involving the upper arm and 30 healthy controls. Magnetic resonance neurography was performed at 3 T using transverse T2-weighted (T2-w) turbo spin echo and spin echo planar imaging diffusion-weighted sequences. T2-weighted normalized signal (nT2), fractional anisotropy (FA), apparent diffusion coefficient (ADC), radial diffusivity (RD), and axial diffusivity (AD) of the median, ulnar, and radial nerves were quantified after manual segmentation. Diagnostic performance of each separate parameter and combinations of parameters was assessed using the area under the receiver operating characteristic curve (AUC). Bootstrap validation was used to adjust for potential overfitting. - Results - Average nT2, ADC, RD, and AD values of the median, ulnar, and radial nerve were significantly increased in neuropathy patients compared with that in healthy controls (nT2, 1.49 ± 0.05 vs 1.05 ± 0.05; ADC, 1.4 × 10−3 ± 2.8 × 10−5 mm2/s vs 1.1 × 10−3 ± 1.3 × 10−5 mm2/s; RD, 9.5 × 10−4 ± 2.9 × 10−5 mm2/s vs 7.2 × 10−4 ± 1.3 × 10−5 mm2/s; AD, 2.3 × 10−3 ± 3.7 × 10−5 mm2/s vs 2.0 × 10−3 ± 2.2 × 10−5 mm2/s; P < 0.001 for all comparisons). Fractional anisotropy values were significantly decreased in patients (0.51 ± 0.01 vs 0.59 ± 0.01; P < 0.001). T2-weighted normalized signal and DTI parameters had comparable diagnostic accuracy (adjusted AUC: T2-w, 0.92; FA, 0.88; ADC, 0.89; AD, 0.84; RD, 0.86). Combining DTI parameters significantly improved the diagnostic accuracy over single-parameter analysis. In addition, the combination of nT2 with DTI parameters yielded excellent adjusted AUCs up to 0.97 (nT2 + FA). - Conclusions - Diffusion tensor imaging has high diagnostic accuracy in peripheral neuropathy. Combining DTI with T2 can outperform T2-w imaging alone and provides added value in magnetic resonance neurography.
Gesehen am 28.05.2020